2013
DOI: 10.1021/jz4024018
|View full text |Cite
|
Sign up to set email alerts
|

Roaming Dissociation of Ethyl Radicals

Abstract: Previous studies on the photodissociation of C2H5 reported rate constants for H-atom formation several orders of magnitude smaller than that predicted by Rice-Ramsperger-Kassel-Marcus (RRKM) theory. This Letter provides a potential explanation for this anomaly, based on direct trajectory calculations of C2H5 dissociation. The trajectories reveal the existence of a roaming dissociation channel that leads to the formation of C2H3 and H2. This channel is found to proceed over the ridge between the transition stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 30 publications
0
35
0
Order By: Relevance
“…189 Direct dynamics calculations have variously suggested roles for a minor channel leading to electronically excited triplet C2H4(ã 3 B1u) + H products, 192 and for a roaming channel leading to H2 + C2H3 products. These C2H3 products are then proposed to release an H atom, which could offer a possible rationale for the reported slow build-up rate of the atomic products, 193 though it is difficult to reconcile the observed H atom velocity distribution with such a mechanism. 194 Finally, we note that C-C bond fission is also thermodynamically allowed when exciting in this wavelength range, but we are not aware of any reports of such product formation.…”
Section: Alkyl Radicalsmentioning
confidence: 99%
“…189 Direct dynamics calculations have variously suggested roles for a minor channel leading to electronically excited triplet C2H4(ã 3 B1u) + H products, 192 and for a roaming channel leading to H2 + C2H3 products. These C2H3 products are then proposed to release an H atom, which could offer a possible rationale for the reported slow build-up rate of the atomic products, 193 though it is difficult to reconcile the observed H atom velocity distribution with such a mechanism. 194 Finally, we note that C-C bond fission is also thermodynamically allowed when exciting in this wavelength range, but we are not aware of any reports of such product formation.…”
Section: Alkyl Radicalsmentioning
confidence: 99%
“…33 Matsugi identified a roaming pathway in trajectory calculations on ethyl, leading to vinyl + H 2 . 34 He suggested that part of the previously observed H-atoms might originate from the photodissociation of vinyl. However, the observed H-atom translational energy release does not seem to be in agreement with this pathway.…”
Section: Introductionmentioning
confidence: 99%
“…This is, presumably, an artifact of the short time approximation that we used in the derivation of Eq. (10). Indeed, it is easy to check that Eq.…”
Section: Theorymentioning
confidence: 91%
“…Indeed, it is easy to check that Eq. (10) conserves energy approximately, up to the leading order in E = E 2 − E 1 . Furthermore, we have run the test problems considered below using condition of Eq.…”
Section: Theorymentioning
confidence: 99%
See 1 more Smart Citation